Optimizing the Combined Allocation of Land and Water to Agriculture in the Omo-Gibe River Basin Considering the Water-Energy-Food-Nexus and Environmental Constraints - Sintayehu Legesse Gebre; Jos Van Orshoven; Dirk Cattrysse (Land, 2023)
This study applied the Gebre optimization model to optimize the land and water usage in the Omo-Gibe river basin, Ethiopia, where competition among stakeholders and growing demands pose a challenge. This model was applied through a nexus approach to maximize benefits and minimize conflicting trade-offs. The main objective was to maximize the economic benefit from land and water allocation with the framework of the land-water-food-energy-environment nexus under climate change mitigation and river ecosystem services (LWFEEN). This model takes into account multiple dimensions, including economic, environmental, social, and technical factors, going beyond ordinary optimization models. It also incorporates an innovative crop succession allocation concept not often seen in the literature. This crop succession proposal includes sequences of cropping patterns and fallow land use options that closely resemble real-world farming practices. The results demonstrated that the Gebre optimization model effectively resolves the existing constraint conflicts and maximizes economic benefits by reducing costs, penalties, and environmental impacts, promoting sustainable use of natural resources in the Omo-Gibe river basin and avoiding conflicts among stakeholders. Therefore, this study offered decision-makers a strategic perspective on how to apply the Gebre-model within the context of the land-water-food-energy-environment nexus(LWFEEN) approach in river basins such as the Omo-Gibe, with the ultimate goal of achieving sustainable development.